Molecular biology interventions for activity improvement and production of industrial enzymes. (March 2021) - Kant Bhatia, Shashi; Vivek, Narisetty; Kumar, Vinod; Chandel, Neha; Thakur, Meenu; Kumar, Dinesh; Yang, Yung-Hun; Pugazendhi, Arivalagan; Kumar, Gopalakrishnan
Graphical abstract: Highlights: Enzymes can perform catalysis under ambient conditions with minimum side products. Metagenomics is a powerful tool to discover novel enzymes. Directed evolution and site-directed mutagenesis used to improve enzyme activity. New enzymes can be designed using bioinformatics and metabolic engineering tools. Abstract: Metagenomics and directed evolution technology have brought a revolution in search of novel enzymes from extreme environment and improvement of existing enzymes and tuning them towards certain desired properties. Using advanced tools of molecular biology i.e. next generation sequencing, site directed mutagenesis, fusion protein, surface display, etc. now researchers can engineer enzymes for improved activity, stability, and substrate specificity to meet the industrial demand. Although many enzymatic processes have been developed up to industrial scale, still there is a need to overcome limitations of maintaining activity during the catalytic process. In this article recent developments in enzymes industrial applications and advancements in metabolic engineering approaches to improve enzymes efficacy and production are reviewed.